A macroeconometric model for the Euro economy - Christian Dreger (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2003)
In this paper a structural macroeconometric model for the Eurozone is presented. In opposite to the multi country modelling approach, the model relies on aggregate data on the supra-national level. Due to nonstationarity, all equations are estimated in an error correction form. The cointegrating relations are derived jointly with the short-run dynamics, avoiding the finite sample bias of the two step Engle Granger procedure. The validity of the aggregated approach is confirmed by out-of-sample forecasts and two simulation exercises. In particular the implications of a lower economic recovery in the US and a shock in the nominal Euro area interest rate are discussed.
urn:nbn:de:gbv:3:2-20499
Keywords: C3; C5; F01; 330; Euro area economy; macroeconometric models; error correction; Ökonometrisches Makromodell; Eurozone; EU-Staaten